1996
DOI: 10.1039/dt9960002309
|View full text |Cite
|
Sign up to set email alerts
|

Substituent-controlled assembly of helical complexes: synthesis, crystal and molecular structures of double helical silver(I) complexes with substituted quinquepyridines

Abstract: Both 6.6""-dimethyl-(dmqpy) and 6,6""-dimethyl-4',4'"-diphenyl-2,2' : 6',2" : 6",2"' : 6"',2""-quinquepyridine (dmpqpy) have been found to form dinuclear double helical silver(1) complexes [Ag,(dmqpy),][ClO,], 1 and [Ag2(dmpqpy)2][C10,]2~2H20 2. The introduced terminal methyl groups play a crucial role in the assembly processes. According to their crystal structures, the ligand adopts the usual [2 + 31 co-ordination mode in 1 and the silver(1) is five-co-ordinated with a flattened and distorted trigonal-bipyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Despite the covalence of the bonding to each silver atom in the compound, the AgϪN distances are within the expected range. The Ag(1)···Ag (2) [31] These values are in accordance with a shorter silver···silver contact. It has been suggested that it is the steric effect of the terminal groups in flexible ligands with various donor atoms that forces the ligand to adopt a double helical disposition, since the planar configuration is not possible.…”
Section: Crystal Structure Of [Ag(fc 2 Qpy)]otfsupporting
confidence: 73%
See 4 more Smart Citations
“…Despite the covalence of the bonding to each silver atom in the compound, the AgϪN distances are within the expected range. The Ag(1)···Ag (2) [31] These values are in accordance with a shorter silver···silver contact. It has been suggested that it is the steric effect of the terminal groups in flexible ligands with various donor atoms that forces the ligand to adopt a double helical disposition, since the planar configuration is not possible.…”
Section: Crystal Structure Of [Ag(fc 2 Qpy)]otfsupporting
confidence: 73%
“…In Figure 4, we show a comparison of the calculated AgϪAg and AgϪN distances (Å ) with those found in the corresponding section of the experimental structure of the [Ag 2 (Fc 2 qpy) 2 ] 2ϩ helix (notice that for clarity, silver atoms are represented twice, as each chain binds two silvers), and also of the [Ag 2 (dmqpy) 2 ] 2ϩ complex (owing to symmetry, only one set of distances is given). [31] Although the AgϪAg distance is either slightly too long or too short, depending on the structure considered, some AgϪN distances compare relatively well. Each helix binds two different Ag atoms, using three N atoms for the first Ag, and two N atoms for the second.…”
Section: Theoretical Studiesmentioning
confidence: 93%
See 3 more Smart Citations